The constitution of Indonesia : a contextual analysis - Butt, Simon; Lindsey, Timothy , 1962- (Constitutional systems of the world, 2012)
For decades, Indonesia's 1945 Constitution, the second-shortest in the modern world, was used as an apologia by successive authoritarian regimes. But following the fall of President Soeharto in 1998 the amendment of the Constitution ushered in a liberal democratic system. This book surveys this remarkable constitutional transition